Should the ECB adjust its strategy in the face of a lower r*? - Philippe Andrade; Jordi Galí; Hervé Le Bihan; Julien Matheron (Federal Reserve Bank of Boston, 2022)
We address the question in this paper's title using an estimated New Keynesian DSGE model of the euro area with trend inflation, imperfect indexation, and a lower bound on the nominal interest rate. In this setup, a decrease in the steady-state real interest rate, r*, increases the probability of hitting the lower bound constraint, which entails significant welfare costs and warrants an adjustment of the monetary policy strategy. Under an unchanged monetary policy rule, an increase in the inflation target of eighttenths the size of the drop in the real natural rate of interest is warranted. Absent an increase in the inflation target, and assuming the effective lower bound prevents the European Central Bank from implementing more aggressive negative interest rate policies, adjusting the monetary strategy requires considering alternative instruments or policy rules, such as a commitment to make up for recent, belowtarget inflation realizations.
Keywords: E31; E52; E58; 330; inflation target; effective lower bound; monetary policy strategy; euro area